A Critical Analysis of “Studies in Modern Arabic Literature (Prose)” - Alireza Kahe (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Over the last century, Contemporary Arabic prose has changed widely, so studying its formation and evolution requires careful and comprehensive research because of the geographic extent and the subject. The book entitled “Studies in Modern Arabic Literature (Prose)” by Mohammad Ahmed Rabea and Salem Ahmed Hamdaniis is an example of the various works that have been written in this field. This study, in addition to the historical approach which introduces some selective examples of Arabic prose in contemporary era, tries to introduce its analysis to the readers. in order to find an answer to see whether this book can be introduced as a teaching text for the course of contemporary prose texts for bachelor degree in Arabic Language and Literature or not, it must be said that in order to not to follow the regular approach in analyzing texts, and because of its non- comprehensive examples, it cannotbe introduced as a comprehensive reference book in the field, and it does not meet the needs of students. This article tried to analyze the form and content of the book, and some content weaknesses were found.